Photo finish : - Canfield, Jon (SYBEX, 2004)
If you've ever been overwhelmed by the complexities of optimizing images for output, this results-oriented guide will clear everything up. Photo Finish: The Digital Photographer's Guide to Printing, Showing, and Selling Images shows you how to attain the best possible output for any medium. Digital imaging experts Jon Canfield and Tim Grey combine practical technical information with inspiring examples to teach you how to: get consistently great prints, mount and frame your work, create compelling photo slideshows, build attention-grabbing photo websites, get your work shown in exhibitions and galleries, and sell your images online. While other books focus on one aspect of output, this comprehensive guide covers all the ways you can share your images.